Chemical Markers for Differentiating Yellow Prickly Pear (Opuntia ficus-indica) from Southern Greece: Insights from Physicochemical Parameters, Elemental Composition, Antioxidants, and Vitamins - Artemis P. Louppis; Michael G. Kontominas; Michalis S. Constantinou; Ioanna S. Kosma; Anastasia V. Badeka; Georgios Stamatakos (Molecules)
This study presents an innovative approach to differentiate Southern Greek yellow prickly pear samples according to geographical origin based on physicochemical parameters, mineral composition, and bioactive compounds using advanced chemometrics. A total of 56 yellow prickly pear samples were collected from four distinct Greek regions (Crete, Paros, Symi, Peloponnese) during the 2019 and 2020 harvest seasons. A multi-platform analytical strategy was employed, combining classical physicochemical analyses and UV spectrophotometry for total antioxidant activity with cutting-edge techniques such as UPLC-MS/MS for precise quantification of vitamins and antioxidants, and ICP-MS for mineral profiling. In total, thirteen physicochemical parameters, nineteen macro-, micro-, and trace elements, nine vitamins, and seven antioxidants were identified and quantified. Application of MANOVA and Linear discriminant analysis (LDA) revealed that eight physicochemical parameters, ten mineral elements, and sixteen bioactive compounds played a crucial role in sample geographical differentiation. The classification success rates using the cross-validation method were 82.1% for physicochemical parameters, 75.0% for minerals, and an impressive 96.4% for vitamins and antioxidants highlighting the robust tool for the geographical differentiation of Southern Greek yellow prickly pears.